The Unified Theory of Acceptance and Use of Technology (UTAUT) Method in Evaluating Hospital Management Information Systems - La’a, Modestus; Tangdililing, Mariane Lukytha; Paramarta, Vip (Journal of Midwifery and Nursing, 2024)
Hospital management information systems play an important role in managing patient care together. Technology acceptance models such as the Unified Theory of Acceptance and Use of Technology (UTAUT) have proven important for predicting information technology acceptance. This literature review aims to evaluate the extended UTAUT model to predict hospital management information systems represented by behavioral intention, convenience, and ease of collaboration. The methods used in this paper are literature review, collection and analysis of scientific articles, and other scientific sources. The results of the literature review show that UTAUT can be a theoretical approach that supports hospital management information systems